2004
DOI: 10.1111/j.1523-1755.2004.00880.x
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of erythropoietin levels in patients with various degrees of renal insufficiency and anemia

Abstract: A cut-off level for an altered set point of erythropoietin regulation was determined at 40 mL/min creatinine clearance. Above this cut-off hemoglobin negatively regulates erythropoietin. Below the cut-off erythropoietin levels remain stable. Pathophysiologic concepts for this finding and clinical implications in patients with moderate renal failure are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
72
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(86 citation statements)
references
References 18 publications
7
72
0
1
Order By: Relevance
“…Fehr et al (9) first suggested that it began below a GFR of 40 ml/min per 1.73 m 2 , but they did not stratify the analysis by anemia status. In this study, we examined the interaction between Hb and GFR according to anemia status and found a slightly lower GFR threshold in patients with anemia (30 ml/min per 1.73m 2 ); this is likely explained by the use of Cockcroft-Gault estimated GFR in the study by Fehr et al (9), whereas we used mGFR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fehr et al (9) first suggested that it began below a GFR of 40 ml/min per 1.73 m 2 , but they did not stratify the analysis by anemia status. In this study, we examined the interaction between Hb and GFR according to anemia status and found a slightly lower GFR threshold in patients with anemia (30 ml/min per 1.73m 2 ); this is likely explained by the use of Cockcroft-Gault estimated GFR in the study by Fehr et al (9), whereas we used mGFR.…”
Section: Discussionmentioning
confidence: 99%
“…In patients without CKD, EPO and hemoglobin (Hb) levels are negatively correlated, a feedback regulation that tends to be reversed in CKD patients. (7)(8)(9) In ESRD patients, the feedback regulation process is blunted, even though it is somewhat preserved after hemorrhage (10,11) and possibly at high altitudes (12). EPO levels remain in the normal range in CKD patients compared with non-anemic healthy controls (7,13,14).…”
Section: Introductionmentioning
confidence: 99%
“…Serum erythropoietin deficiency is often relative and, in advanced CKD, usually does not correlate with the degree of anemia (84,85). Even in patients with kidney failure treated with dialysis, the ability to upregulate erythropoietin production in response to acute anemia is preserved (86,87).…”
Section: Other Selected Recommendations Under Considerationmentioning
confidence: 99%
“…Endogenous EPO is mainly of renal origin. The concentration of the hormone is abnormally low when related to the hemoglobin level ([Hb]) in CKD [43]. The anemia in CKD patients is often aggravated due to accompanying inflammatory processes, reduced iron availability, hemolysis, blood losses, nutritional deficiencies, and hyperparathyroidism [44].…”
Section: Clinical Use Of Rheposmentioning
confidence: 99%